2021
DOI: 10.3390/ijms22158263
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Responses of Six Apple Rootstocks to Osmotic Stress

Abstract: The growth and productivity of several apple rootstocks have been evaluated in various previous studies. However, limited information is available on their tolerance to osmotic stress. In the present study, the physiological and molecular responses as well as abscisic acid (ABA) levels were assessed in six apple rootstocks (M26, V3, G41, G935, B9 and B118) osmotically stressed with polyethylene glycol (PEG, 30%) application under greenhouse conditions. Our results showed that V3, G41, G935 and B9 had higher re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…A recent study found that OsWRKY29 could act as a new ABA signaling repressor for seed dormancy in rice with RNAi mutant lines displaying greater sensitivity after ABA treatment (Zhou et al 2020). The WRKY29 gene was negatively correlated with the ABA content, and down-regulated in the tolerant rootstocks under osmotic stress (Hezema et al 2021). RBOHA is a burst oxidase homolog protein, which participates in diverse biological processes in higher plants (Arthikala and Quinto 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that OsWRKY29 could act as a new ABA signaling repressor for seed dormancy in rice with RNAi mutant lines displaying greater sensitivity after ABA treatment (Zhou et al 2020). The WRKY29 gene was negatively correlated with the ABA content, and down-regulated in the tolerant rootstocks under osmotic stress (Hezema et al 2021). RBOHA is a burst oxidase homolog protein, which participates in diverse biological processes in higher plants (Arthikala and Quinto 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The RWC is an important indicator of water status in plants because it reflects the balance between water supply to the tissues and transpiration rate [ 67 ]. Reductions in RWC under salt and osmotic stress, caused by low osmotic potential, are commonly reported in the literature [ 68 , 69 ]. In detail, it has been argued that salt-tolerant plants decrease the hydraulic conductance of their roots, thereby reducing the delivery of (salty) water to the shoot and resulting in reduced water potential in their leaves [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, up-regulation of WRKY29 in the BpHOX2 transgenic B. platyphylla may lead to an increase in susceptibility to PEG-mediated osmotic stress. Hezema et al [102] demonstrated that in apple rootstocks under hard osmotic stress WRKY29 acts as a negative regulator of ABA-mediated stomatal closure, which can lead to water leakage. Thus, the WRKY29 gene is down-regulated under osmotic stress in apple rootstocks.…”
Section: Peg-mediated Osmotic Stressmentioning
confidence: 99%
“…Thus, the drought and the PEG-mediated osmotic stress in B. platyphylla induced the expression of many genes of the ROS scavenging enzymes and their TFs, activation of water deprivation and mechanical damage responses, and cell wall protection. In addition, it can be assumed that there is a system for the formation of an adequate stress response, which implies a balance between tolerance and susceptibility by controlling of ABA-mediated stomatal movement [97,102].…”
Section: Peg-mediated Osmotic Stressmentioning
confidence: 99%